Renal angiomyolipoma in patients with tuberous sclerosis complex: findings from the TuberOus SClerosis registry to increase disease Awareness. Issue 3 (25th April 2018) - Kingswood, J Chris; Belousova, Elena; Benedik, Mirjana P; Carter, Tom; Cottin, Vincent; Curatolo, Paolo; Dahlin, Maria; D' Amato, Lisa; d'Augères, Guillaume Beaure; de Vries, Petrus J; Ferreira, José C; Feucht, Martha; et al.
Abstract: Background: Renal angiomyolipoma occurs at a high frequency in patients with tuberous sclerosis complex (TSC) and is associated with potentially life-threatening complications. Despite this frequency and severity, there are no large population-based cohort studies. Here we present baseline and follow-up data of the international TuberOus SClerosis registry to increase disease Awareness (TOSCA) with an aim to provide detailed clinical characteristics of renal angiomyolipoma among patients with TSC. Methods: Patients of any age with a documented clinic visit for TSC within 12 months or who were newly diagnosed with TSC before participation in the registry were eligible. Data specific to renal angiomyolipoma included physical tumour characteristics (multiple, bilateral, lesion size and growing lesions), clinical signs and symptoms, and management. The effects of age, gender and genotype on the prevalence of renal angiomyolipoma were also evaluated. Results: Renal angiomyolipoma was reported in 51.8% of patients at baseline, with higher frequency in female patients (57.8% versus 42.2%). The median age at diagnosis was 12 years. Prevalence of angiomyolipoma was higher in patients with TSC2 compared with TSC1 mutations (59.2% versus 33.3%, P < 0.01). Of the 1031 patients with angiomyolipoma at baseline, multiple lesions were reported in 88.4% and bilateral in 83.9% of patients, while the size of angiomyolipoma was >3 cm in 34.3% of patients. Most patients were asymptomatic (82%). Frequently reported angiomyolipoma-related symptoms included bleeding, pain, elevated blood pressure and impaired renal function. Embolization and mammalian target of rapamycin inhibitors were the two most common treatment modalities. Conclusions: The TOSCA registry highlights the burden of renal angiomyolipoma in patients with TSC and shows that renal manifestations are initially asymptomatic and are influenced by gender and genotype. Furthermore, the occurrence of significant problems from angiomyolipoma in a minority of younger patients suggests that surveillance should begin in infancy or at initial diagnosis.